Influence of relative force on allaround competition result with gymnasts - Paunovic, M.; Velickovc, S.; Durovic, M.; Okicic, T.; Stojanovic, N.; Milosevic, N. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The aim of this study was to investigate the influence of the relative force of different muscle groups on the result in all-around competition. The sample of respondents for the research purposes consisted of 16 gymnasts from Serbia, Bulgaria, Slovenia, Austria, Croatia, Switzerland and South Africa, aged 14 to 16 (avg 15,19) and body weight from 33 kg to 58 kg (avg 44,38 kg). Respondents had a training experience from six to nine years (avg 7.44). For the assessment of maximum muscle force were measured: maximum muscle force of back extensors (BACMAX), maximum muscle force of knee extensors (LEGMAX), maximum muscle force of the upper arm flexors (BICMAX) and maximum force of the shoulder muscles (SHOMAX). The Japanese digital IMADA Z2H 100 with the WinWedge 3.4 software was used to measure the maximum muscle force of the above mentioned muscle groups. For the evaluation of the results in all-around competition the sum of "D" and "E" score on all apparatus was used (SCORE). For all variables descriptive statistics and regression analyse were used in order to determine the influence of muscle force on result in all around competition. The results of the regression analysis have shown that there is no statistically significant influence of the set of variables on the result in the all-around (p = 0.653), nor with any variable in particular (BACMAX = 0.841, LEGMAX = 0.413, BICMAX = 0.926, SHOMAX = 0.149). The reason for the results obtained in this study should be sought in the age of the respondents. Namely, at this age, the result is influenced by a number of factors. One of them is the technical preparation of gymnasts as well as level of training. Another factor influencing the result is the number of competitions at which gymnasts participated. A larger number of competitions allows competitor to gain the necessary experience and reduce the influence of nervousness and anxiety on the result. Finally it should be noted that this study is an excellent base for further researches of muscular force in artistic gymnastics on a different sample of respondents and different muscle groups.